2017
DOI: 10.5897/jdoh2017.0219
|View full text |Cite
|
Sign up to set email alerts
|

Oral hygiene practice of adult diabetic patients and their awareness about oral health problems related to diabetes

Abstract: Diabetes mellitus is a major public health problem in the Kingdom of Saudi Arabia. Several studies have shown that diabetic patients are at a greater risk of developing oral health problems than non-diabetics. This study aims to evaluate the oral hygiene practices of adult diabetic patients and their awareness of oral health problems related to the disease. In this cross-sectional, Internet-based descriptive study, a self-administered questionnaire was uploaded online and any adult diabetic patient living in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
0
14
1
Order By: Relevance
“…The oral health screening status in this study was almost consistent with the findings; 27% in India, 22 17% and 33.3% in Malaysia, during 2016 and 2012. 10,27 In this study, the level of oral health screening was higher than the findings; 12.6% and 15.1% in Saudi Arabia, 28,29 and 10% in Jordan. 30 This difference might be due to variations in types of population demographics and study time.…”
Section: Discussioncontrasting
confidence: 64%
“…The oral health screening status in this study was almost consistent with the findings; 27% in India, 22 17% and 33.3% in Malaysia, during 2016 and 2012. 10,27 In this study, the level of oral health screening was higher than the findings; 12.6% and 15.1% in Saudi Arabia, 28,29 and 10% in Jordan. 30 This difference might be due to variations in types of population demographics and study time.…”
Section: Discussioncontrasting
confidence: 64%
“… 22 A study by Al Amassi and Al Dakheel found only 15.1% of diabetic patients regularly visiting the dentist in Saudi Arabia. 23 Similarly, a low prevalence of dental visits in the last year (13%) among diabetic patients in Riyadh was reported by Bahammam. 24 Likewise, only 14% of diabetic patients in the United Arab Emirates were found to visit a dentist for a regular dental check-up.…”
Section: Discussionmentioning
confidence: 74%
“…This is contrary to a study of diabetic patients by Al Amassi and Al Dakheel who reported that social media was the main source of oral health information followed by dentists and dental hygienists. 23 Almaiman et al showed that 67.7% of social media users seek online oral health related information in Saudi Arabia. 32 In the present study, 30.70% of patients indicated social media as an important source of oral health education.…”
Section: Discussionmentioning
confidence: 99%
“…Out of 1317 questions asked in these surveys, 553 items were used to measure participants’ knowledge and awareness [ 2 , 6 , 7 , 12 , 14 – 36 , 38 , 40 – 43 , 45 – 52 ]. Two hundred twenty-six other items were used to determine participants’ attitudes toward oral health [ 2 , 6 , 7 , 12 – 14 , 17 , 19 , 21 – 23 , 28 , 31 , 32 , 36 , 38 , 43 , 46 – 48 , 51 , 52 ]. Meanwhile, only 149 items assessed oral hygiene practices [ 2 , 12 , 14 , 15 , 24 , 25 , 31 , 34 – 36 , 38 , 42 , 47 – 51 ].…”
Section: Resultsmentioning
confidence: 99%